EVALUASI PELAKSANAAN PELAYANAN KESEHATAN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH KABUPATEN BATUBARA, SUMATERA UTARA PASKA OTONOMI DAERAH - Pasaribu, Pangeran Indra; Marom, Aufarul; Fathurrochman, Fathurrochman (Journal of Public Policy and Management Review, 2015)
District of Batubara is one of the coastal region in North Sumatera with a huge economy potential. In 2012 regional income per capita District of Batubara at 55,13 million rupiah and the highest in NorthSumatraProvince. Yet District of Batubara has district health problem because the District of Batubara is the coastal area. This study using a qualitative research .Besides through interviews and official documents , in this study done technique to calculate the value of achievement between the target and the realization of the implementation of the field of health in-patients at The Disctrict of BatubaraGeneral Hospital after regional autonomy .By means of this kind of analysis , it will be known to the achievement of the results of the implementation of the field of health in-patients at The Disctrict of BatubaraGeneral Hospital. Two programs that have been conducted by in-patient installation The Disctrict of BatubaraGeneral received a value of the achievement of activities as much as 82 % and 87 %.With weights each 50 percent of the value of the achievement of then program in-patient installation is as much as 84,5 % and it is categorized successfully or good .